UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI SEKOLAH DASAR - Sabrina Ramadhani; Siti Dewi Maharani; Vinencia Ika Indralin (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
Abstract The background of this research is the finding of problems that arise in the content of mathematics lessons in class IV.A of SD Negeri 112 Palembang. The problem is the low mathematics learning outcomes in fractional material. The reason is that learning still uses the lecture method. The corrective action chosen is the application of the problem-based learning model. The subjects of this study were 42 class IV.A students at SD Negeri 112 Palembang. Data collection techniques using observation, tests and documentation. The data analysis technique used is a qualitative descriptive approach and descriptive statistics. This classroom action research was conducted in two cycles, with the results of the research showing that the application of the problem-based learning model to the mathematics lesson content had a positive impact on student learning outcomes. The increase in student learning outcomes can be seen from the percentage increase in cycle I by 57%, then it increased in cycle II by 83%. Thus this research can be said to be successful in improving student learning outcomes through the application of problem-based learning models. Keywords: Mathematics, Learning outcomes, Problem Based Learning Models